(untitled) (Physical Education, Health and Social Sciences, 2025)
Background: Total knee replacement (TKR), patients often experience deficits in balance, proprioception, and joint stability. Stretching is commonly included in rehabilitation, but its specific effects on stability and balance are not fully elucidated. Objective: To review evidence on the impact of stretching interventions alone /combined on knee joint stability and balance following TKR. Design: Narrative review to evaluate the impact of stretching on knee joint stability and balance after total knee replacement. Methods: Relevant peer‑reviewed literature (2020–2025) was identified via databases, examining stretching as part of postoperative physiotherapy for Total knee replacement. Key outcomes included postural control, balance measures, and range of motion (ROM). Results: Evidence supports that stretching improves ROM and reduces stiffness. However, isolated stretching has limited direct impact on objective measures of balance and stability. Studies showing significant improvements in balance typically include combined programs such as strength, balance and task-specific training. Heterogeneity in dosing, timing, and outcome measures limits definitive conclusions. Conclusion: Stretching is valuable for ROM recovery after Total knee replacement, but to meaningfully improve balance and joint stability, it should be integrated into a multimodal rehabilitation regimen. Future research should focus on standardized balance outcome measures and better-defined stretching protocols.